Pengaruh Model Pembelajaran Self Directed Learning Terhadap Kemampuan Koneksi Matematis Siswa Kelas X SMA Negeri 1 Sosa - Hasibuan, Sundut Azhari; Sucihati, Rizkina; Siregar, Syarimah (Manna wa Salwa Foundation (Yayasan Manna wa Salwa), 2025)
This research is a quasi-experimental study with a population of Class X students at SMA Negeri 1 Sosa Academic Year 2024/2025. The sample in this study is Class X-5 as the experimental class and Class X-2 as the control class. The experimental class is taught using the self directed learning model while the control class is taught using the conventional learning model. The aim of this research is to determine whether the self directed learning model has an effect on the mathematical connection skills of Class X students at SMA Negeri 1 Sosa Academic Year 2024/2025. The results of the hypothesis test indicate that the t-value with equal variances assumed is 5.287 with a t-table value of 1.677. Thus, the t-value > t-table, meaning H0 is rejected and H1 is accepted. The results of the above-mentioned test concluded that there is an influence of the self-directed learning model on the mathematical connection skills of students in class X at SMA Negeri 1 Sosa for the 2024/2025 academic year. The percentage of mastery of mathematical connection indicators is always higher in the experimental class compared to the control class. The best connection skill indicator in the experimental class is indicator 2, which is understanding how mathematical ideas are connected and built upon each other in a comprehensive way at 88.90%. Different results were found in the control class, where the best connection skill indicator was indicator 3, which is recognising and using mathematics in contexts outside of mathematics at 74.47%..